General model of high performance computing - Gamayun, V.P. (Problems of Informatization and Management, 2022)
The manual model for high velocity processing is proposed.Model is oriented multioperand processing in massive architecture. The processing.elements is n onbinar type. The cvazigrafcal processing is new method to increasing multioperand processing Macrooperator methods is instrument for changing of program. Velocity realization in this case is increasing with using convertor. The multioperand processing in massive architecture is result the model processing. Model is open system, which can work to additional methods.